2011
DOI: 10.2174/156720111794479925
|View full text |Cite
|
Sign up to set email alerts
|

Newer Approaches for Optimal Bioavailability of Ocularly Delivered Drugs: Review

Abstract: Eye diseases can cause discomfort and anxiety in patients, with the ultimate fear of loss of vision and facial disfigurement. Many regions of the eye are relatively inaccessible to systemically administered drugs and, as a result, topical drug delivery remains the preferred route in most cases. Drugs may be delivered to treat the precorneal region for conjunctivitis and blepharitis, or to provide intraocular diseases such as glaucoma, uveitis, and cytomegalovirus retinitis. Most of the ophthalmic formulation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Unfortunately, the presence of fibrotic tissue at the anterior surface of the eye after an injury or a surgery may induce corneal opacification (corneal haze) [120] and may lead to surgical failure. Different approaches to regenerate the ocular surface and to treat the scar formation have been attempted [121]. Results demonstrated that different blood formulations (whole plasma and PRP) showed similar biological effects on proliferation and migration of keratocytes and conjunctival fibroblast cells and on the inhibition of myofibroblastic phenotype to reduce scarring [110].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Unfortunately, the presence of fibrotic tissue at the anterior surface of the eye after an injury or a surgery may induce corneal opacification (corneal haze) [120] and may lead to surgical failure. Different approaches to regenerate the ocular surface and to treat the scar formation have been attempted [121]. Results demonstrated that different blood formulations (whole plasma and PRP) showed similar biological effects on proliferation and migration of keratocytes and conjunctival fibroblast cells and on the inhibition of myofibroblastic phenotype to reduce scarring [110].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Many attempts have been made to prolong the exposure time of topically applied ocular treatments and to improve their bioavailability, therapeutic efficacy, or patient compliance by reducing the number of required administrations [810]. Hydrogels, now widely used in the ophthalmic pharmaceutical industry, have enabled, for example, a decrease in the frequency of timolol administrations from two instillations daily to only one.…”
Section: Cationic Nanoemulsion For Ocular Deliverymentioning
confidence: 99%
“…Superficial barriers impede direct and systemic drug access to the specific site of action. Drug loaded nanoparticles show favorable biological properties including prolonged residence time for eye drops, decreased toxicity, and increased ability of the drug to penetrate into the deeper layers of the ocular structure and aqueous humor thus minimizing precorneal drug loss caused by rapid tear fluid turnover [6,26]. Techniques were planned to transform nanoparticles from lipophilic to hydrophilic and to down-regulate irritation to the eye.…”
Section: Design Considerations For Ocular Drug Nanomaterialsmentioning
confidence: 99%